Studies in Health Technology and Informatics Volume 2 - Christensen, Jens Pihlkjaer (IOS Press, 2014)
The AIM Exploratory Action, 1988-1990, was an R&D Programme for the application of Information Technologies and Telecommunications, IT&T, in medicine and health care. This book is about the achievements of this programme. At the time it is published, those achievements are already being utilised in the successor, namely Telematics in Health Care, which is an area under the present programme Telematics in Areas of General Interest.